THE CHOICE OF TOPICS IN MALE, FEMALE AND MIXED-SEX GROUPS OF STUDENTS OF PETRA CHRISTIAN UNIVERSITY IN THEIR CHATTING - Nugroho, Aylanda Dwi; Agustin, Shierly (k@ta: A Biannual Publication on the Study of Language and Literature, 2005)
This study analyzed some conversations in the male, female and male-female groups of some university students. Using McCarthy's classification of topics, the results show that 'Persons' is the typical topic in the female group, while 'Objects/ belongings' is the most favorite topic in the male group. In the mixed-sex group, it is interesting to see how both sexes negotiated the topics by proposing the typical topics of the other sex group.